Communicative aspect of studying of features of the scientific speech (Eurasian Journal of Philology Science and Education, 2016)
In this article forms and types of speech activity in system of communicative situations are considered, various stages of scientific and technical cooperation are analyzed. The first year university students of the Kazakh departments studying Russian according to the program of discipline «Professionally oriented Russian language» learn a quite extensive volume of lexical and grammatical material. On the basis of educational and scientific texts students get acquainted with a wide range of data on their specialty and as a result get a large supply of terms and syntactic structures, typical for the language of this specialty. Textbooks on scientific style of Russian and the concrete situations which future specialists meet in theirpractical professional activity aren’t considered. It means that more attention should be paid to the communicativefunctional aspect which can be realized in the course of training on the specialty language. Therefore one of the main objectives of the course «Professionally oriented Russian language» is not further expansion of a stock of terminological lexis which future young specialists have to acquire, but training students’ abilities to cope with the communication situations which can appear in their practical professional work.
Keywords: speech situation; speech activity; scientific style; commu nicative methods; terminology of texts; terminological vocabulary